2019
DOI: 10.1103/physrevd.100.113001
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning classification: Case of Higgs boson CP state in Hττ decay at the LHC

Abstract: Machine Learning (ML) techniques are rapidly finding a place among the methods of High Energy Physics data analysis. Different approaches are explored concerning how much effort should be put into building highlevel variables based on physics insight into the problem, and when it is enough to rely on low-level ones, allowing ML methods to find patterns without explicit physics model.In this paper we continue the discussion of previous publications on the CP state of the Higgs boson measurement of the H → ττ de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…In response to the problems in determining the polarizations, a novel approach has been introduced into high energy physics (HEP). It has been shown that, the artificial neural network (ANN) can be very powerful in determining the polarizations of W, Z bosons [21][22][23] and τ lepton [24]. The ANN approach is one of the machine learning methods, which have been widely used in HEP, and are being developed rapidly in recent years [25][26][27][28][29][30][31][32][33][34].…”
Section: Jhep09(2021)085mentioning
confidence: 99%
“…In response to the problems in determining the polarizations, a novel approach has been introduced into high energy physics (HEP). It has been shown that, the artificial neural network (ANN) can be very powerful in determining the polarizations of W, Z bosons [21][22][23] and τ lepton [24]. The ANN approach is one of the machine learning methods, which have been widely used in HEP, and are being developed rapidly in recent years [25][26][27][28][29][30][31][32][33][34].…”
Section: Jhep09(2021)085mentioning
confidence: 99%
“…Recently, the field of artificial intelligence (AI) has received unprecedented attention, and prodigious progress has been made in the application of the AI techniques [33][34][35][36]. Particularly, the neural network framework that is based on the simulation of the brain has been widely used in many physical researches [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Thus, it is timely to deduce the impact parameter with the new developed machine learning and deep learning algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…It can be implemented in the Monte Carlo simulations as per event spin weight wt, see [15] for more details. In [16,17] we have performed analysis for the three channels of the τ lepton-pair decays, respectively ρ ± ν τ ρ ∓ ν τ , a ± 1 ν τ ρ ∓ ν τ and a ± 1 ν τ a ∓ 1 ν τ but we limited the scope to the scalar-pseudoscalar classification case. We explored the kinematics of outgoing decay products of the τ leptons and geometry of decay vertices.…”
Section: Introductionmentioning
confidence: 99%
“…We analyze possible solutions with Deep Neural Network (DNN) algorithms [4] implemented in Tensorflow environment [18] which we have previously found working well for the binary classification [16,17] between scalar or pseudoscalar Higgs boson variants (which correspond to φ CP = 0 and φ CP = π/2). Our goals for the DNN algorithms is to determine per event:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation